2022
DOI: 10.1101/2022.08.21.22279029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humoral and cellular immune correlates of protection against COVID-19 in kidney transplant recipients

Abstract: As solid organ recipients are at high risk of severe COVID-19 and respond poorly to primary SARS-CoV-2 mRNA vaccination, they have been prioritized for booster vaccination. However, an immunological correlate of protection has not been identified in this vulnerable population. We conducted a prospective monocentric cohort study of 65 kidney transplant recipients who received three doses of SARS-CoV-2 BNT162b2 mRNA vaccination. Associations between symptomatic breakthrough infection (BTI) and vaccine responses,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Finally, we lack data analyzing cellular immunity. Other immune effectors, in particular T lymphocytes, could contribute toward protection in patients with limited vaccine-induced humoral immunity ( KemLin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we lack data analyzing cellular immunity. Other immune effectors, in particular T lymphocytes, could contribute toward protection in patients with limited vaccine-induced humoral immunity ( KemLin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the cross-variant antibody breadth can be extended to the Omicron XBB, as demonstrated in our study. Studies have shown that antibodies and T cell response are associated with risk against breakthrough infection and severe disease in LTRs and kidney transplant recipients (40)(41)(42). However, the diminished humoral responses against Omicron and its sublineages observed in individuals receiving multiple IS regimens can confer sufficient protection against the presently circulating Omicron variants and future SARS-CoV-2 variants remained to be determined.…”
Section: Discussionmentioning
confidence: 99%